A pilot study of an HbA1c chairside screening protocol for diabetes in patients with chronic periodontitis: the dental hygienist's role. Issue 2 (23rd March 2015) - Bossart, M; Calley, KH; Gurenlian, JR; Mason, B; Ferguson, RE; Peterson, T
Abstract: Objective: To assess effectiveness, convenience and cost of point‐of‐care diabetes screenings performed by a dental hygienist for patients with periodontitis, using a diabetes risk questionnaire, periodontal findings and a glycosylated haemoglobin (HbA1c) analyser. Methods: A purposive sample of 50 participants with periodontitis, never diagnosed with diabetes, reporting ≥one diabetes risk factor, were administered an HbA1c test. Spearman's correlation measured relationships between HbA1c and diabetes risk test scores, numbers of missing teeth, percentage of deep pockets ≥5 mm and percentage of bleeding sites (BOP). Cost and time were assessed. Analyses used 0.05 alpha levels. Results: Thirty‐two per cent ( n  = 16) of participants presented HbA1c values indicating prediabetes; one HbA1c value indicated type 2 diabetes, totalling 34% ( N  = 17). No relationships existed between HbA1c values and diabetes risk scores (rs = 0.153; P  = 0.144), numbers of missing teeth ( r  = 0.190; P  = 0.093), percentage of deep pockets (rs = −0.048; P  = 0.370) or percentage of BOP sites (rs = 0.066, P  = 0.324). Direct cost for each HbA1c was $9US, excluding follow‐up medical diagnosis. Mean screening time including patient education was 14 min (SD = 6.2). Fifty‐three per cent ( n  = 9 of 17) of participants with elevated HbA1c values contacted their primary healthcare provider within 2 weeks as recommended. Conclusion: Point‐of‐care HbA1c screenings by dental hygienists were effective and convenient for identifying undiagnosed prediabetes and provide opportunity for interprofessional patient care; cost or lack of dental insurance may inhibit implementation. Identification of patients at risk for diabetes requires further evaluation.